Pemodelan dan Optimasi Pengaruh Variasi Suhu Pirolisis Lambat terhadap Yield dan Nilai Kalor Biochar Tongkol Jagung - Darajat, Zakiyah; Septiani, Mimin; Sukasri, Arifah; Ole, Maria Assumpta Nogo (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Biochar is a solid product derived from biomass pyrolysis with considerable potential as an alternative energy source and functional material. One of the key parameters influencing biochar characteristics is pyrolysis temperature. This study aims to model and optimize the effect of slow pyrolysis temperature variations on the yield and calorific value of biochar produced from corncob feedstock. The pyrolysis process was conducted using a slow pyrolysis method at temperatures of 350, 400, 450, and 490 °C, with a low heating rate and a residence time of 60 minutes. The resulting biochar was characterized through proximate analysis, while its calorific value was determined using a bomb calorimeter. The relationship between pyrolysis temperature and both yield and calorific value was modeled using polynomial regression. Multi-response optimization was subsequently performed using the desirability function approach. The results indicate that increasing the pyrolysis temperature leads to a reduction in biochar yield, while simultaneously increasing fixed carbon content and stabilizing the calorific value at higher temperatures. The regression model demonstrated strong agreement with the experimental data, with a coefficient of determination (R²) of 0.9582, indicating excellent model fit. Multi-response optimization revealed that the optimal pyrolysis temperature was 350 °C, producing a biochar yield of 79.71% and a calorific value of 7050 cal/g. This study provides a scientific basis for determining optimal slow pyrolysis operating conditions to enhance the valorization of corncob waste as a biochar-based renewable energy resource.